Predictors Of Recycling Behaviour Among Residents Of The Klang Valley, Malaysia - Mutang, Jasmine Adela (2008)

(untitled)
Malaysia is facing a crisis in solid waste management due to rapid urbanization and high concentration of population. It was reported that public participation in recycling is still very low despite rigorous campaigns conducted by the government. Three to five percent of solid waste generated in Malaysia is recycled a number that is far below the rate of 15 to 40 percent in developed countries. This study examines the recycling behaviour among urban households within the Klang Valley area. Specifically, the purpose of the study is to identify reported recycling behaviour, to examine sociodemographic and psychological characteristics of recyclers and non-recyclers, to identify why individuals involve in recycling or otherwise and to determine predictors that increase the probability of recycling behaviour among households. A total of 500 respondents were targeted to involve in this study. However, only 342 respondents were successfully interviewed with a response rate of 68.4%. The sampling technique utilized in the data set was multistage sampling. Data analysis technique used consisted of bivariate analysis and logistic regression.Results of this study indicated that, of the 342 respondents, 62% were of non-recyclers and the remaining 38% are recyclers. No significant socio-demographic differences were found between recyclers and non-recyclers except for ethnicity [Pearson χ² (2, N=342) =11.716, p=.001], marital status [Pearson χ² (2, N=342) =23.204, p=.001] and education. There was significant difference in the mean age [M=-3.291, SD=.992; t(340)=3.317, p=.001], household size [M=0.797, SD=0.200, t(340)=3.994, p=.000], values towards the environment [M=4.305, SD=.246, t(340)=-7.063, p=.000] and attitudes towards recycling [M=7.002, SD=.862, t(340)=-8.119, p=.000] for recyclers and non-recyclers. Generally, results for intrinsic and extrinsic motives among recyclers are not clear as respondent tended to be clustered around the middle of the scale with both motives indicating high percentages. The same goes for hindrances to recycling among the nonrecyclers. The findings indicated that recycling efforts in Malaysia were mostly driven by intrinsic motivation which is a good indicator that might facilitate sustainable practices. Individuals appear to be well aware of the need to recycle and will generally do so if given the means. The hindrances to recycling among the non-recyclers were personal situations and inconvenience. However, the non-recyclers were willing to recycle if given the certain opportunities and special recycling services. Thus, the data show that recycling was well accepted by the public as an activity that is worth undertaking so long as the means exist. The results of logistics regression testing for socio-demographic, knowledge and psychological characteristics showed partial significance at a probability level of .050. The result of Hosmer and Lamershow Goodness-of-fit shows total significance at .050. The logistic model that utilizes study data drawn from the 342 samples and the results of the Binomial Logistic Regression indicate that recycling increased among respondents who were single, possess better values towards the environment and better attitudes towards recycling. However, gender, education attainment, different types of employment status, types of accommodation, house ownership, and knowledge of recycling were not found significant. The findings of the study could be used for designing recycling schemes although it is clear that a one-size-fits-all approach is not acceptable. The information from this study will benefit relevant agencies, business corporations, non-governmental organizations, local governments and others to find out more about social and economic instruments and, where appropriate, use them to deal with recycling-related issues (waste management) that fall within their scope of responsibility when considering the format of new recycling programmes.